Innovative development of smart book: Text written English Grammar for English education department students - Habibah, Nur; Oktavia, Diana; Zura, Della Elpa (Indonesian Research Journal in Education |IRJE|, 2025)
The text written English grammar is a developed course within the latest outcome-based education curriculum in the English Education Department, previously referred to as Grammar course. The change in nomenclature signifies a shift in instructional focus. At the same time, the Grammar course generally provides all the rules and structures; the Text Written English Grammar course concentrates specifically on the grammatical rules applied in written contexts, highlighting the use of more precise and more complex sentence structures. The urgency of this research stems from the lack of teaching materials for the Text Written English Grammar course, as well as the challenges in accessing suitable resources for this subject. The research aimed to demonstrate the development of the Text Written English Grammar smart book and to assess the feasibility of this smart book, which is currently under development.” The research employed the research and development method, which includes four main stages: analysis, design, development, implementation, and evaluation.